If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -16 = -22 + 6x Reorder the terms: -16 + 6x = -22 + 6x Add '-6x' to each side of the equation. -16 + 6x + -6x = -22 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 + 0 = -22 + 6x + -6x -16 = -22 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 = -22 + 0 -16 = -22 Solving -16 = -22 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1=3.33 | | Y=8+16 | | 1.9(x-2.7)= | | y=2x^2+12x+21 | | 8/w=6/54 | | 3x-2(8-x)=-16 | | 5x(-3x)=-15x^2 | | 7.20x+5.50y=52.75 | | k/21=14/49 | | 3+6x=5x | | 2b-3=6 | | 13c^5d^5-169cx^4d^3=0 | | 10/16=15/p | | Y=150+10 | | 71/4×1/18 | | C-12=2 | | 4/5=m/35 | | 8+a=7 | | 15(6x-8)=14(x-5)-2 | | x-9-51=918 | | 2a-4=5 | | 6*11y/2 | | 8d=4 | | -16t^2+126t=126+5 | | -16t^2+126t=136+5 | | y=150+-20x | | 7dy+3xy-3xv-7dv=0 | | x+11-19=228 | | (1/3x^8)(1/7x^5) | | 6(11y/2) | | 3y+4=7y-4 | | 25=5x-16 |